Moral structuring of children during the process of obtaining informed consent in clinical and research settings (2020)
Background: Informed consent is an important factor in a child’s moral structure from which different types of doctor–patient relationships arise. Children’s autonomy is currently under discussion in terms of their decent treatment, beyond what doctors and researchers perceive. To describe the influential practices that exist among clinicians and researchers toward children with chronic diseases during the process of obtaining informed consent. Methods: This was a cross-sectional, qualitative study via a subjective and interpretivist approach. The study was performed by conducting semi-structured interviews of 21 clinicians and researchers. Data analysis was performed using the SPSS version 21® and Atlas Ti version 7.0® programs. Results: The deliberative and paternalistic models were influential practices in the physician–patient relationship. In the deliberative model, the child is expected to have a moral awareness of their care. The paternalistic model determined that submission was a way of structuring the child because he or she is considered to be a subject of extreme care. Conclusions: The differentiated objectification [educational] process recognizes the internal and external elements of the child. Informed consent proved to be an appropriate means for strengthening moral and structuring the child.